KEGIATAN EKSTRAKURIKULER SENI TARI KREASI DI SMKS NUSATAMA PADANG - Kurnia, Dandi; Ayuthia Mayang Sari (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2026)
This study aims to describe the implementation of creative dance extracurricular activities at SMKS Nusatama Padang, including the objectives of the activities, the training process, and the challenges faced along with the solutions implemented. This research uses a qualitative approach with a descriptive method. The research subjects consist of extracurricular mentors and students participating in creative dance activities. Data collection techniques were conducted through observation, interviews, and documentation. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The results of the study show that the creative dance extracurricular activities at SMKS Nusatama Padang consist of three stages: the planning stage, the implementation stage, and the evaluation stage. The planning of creative dance extracurricular activities at SMKS Nusatama Padang consists of a schedule of implementation, training materials, and activity objectives which have been clearly designed so that the activities can proceed according to the established plan. The implementation of creative dance extracurricular activities begins with student registration to participate in the creative dance extracurricular, conducting independent practice using YouTube, repeating dance movements that have been learned, and performing dances at guest welcoming events. These creative dance extracurricular activities are showcased at school farewell events, national day commemorations, guest welcoming events and art performances. However, in its implementation, there are several obstacles, such as limited practice time, differences in student abilities, lack of facilities, and uneven student motivation. To overcome these obstacles, the instructor managed time more effectively, provided varied practice methods, and enhanced student motivation through a communicative and appreciative approach. Thus, the creative dance extracurricular activities at SMKS Nusatama Padang play an important role in developing students' non-academic potential and supporting the formation of students' creative, disciplined, and confident character.